2018
DOI: 10.1007/s00330-018-5326-1
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal involvement in Erdheim-Chester disease (ECD): MRI and CT imaging findings and their association with BRAFV600E mutation

Abstract: • Abdominal imaging plays a crucial role in management of Erdheim-Chester disease. • Significant associations exist between BRAF mutation and several abdominal imaging findings. • Considering several associations, evaluating BRAF mutation status is recommended in ECD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…A total of 65% of patients exhibited encasement of the kidney and involvement of the retroperitoneal space, causing renal artery stenosis in 54% of cases and ureteropelvic junction obstruction in 51% of cases [7]. However, a study investigating abdominal involvement during ECD reported that there was no uterine involvement [8].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 65% of patients exhibited encasement of the kidney and involvement of the retroperitoneal space, causing renal artery stenosis in 54% of cases and ureteropelvic junction obstruction in 51% of cases [7]. However, a study investigating abdominal involvement during ECD reported that there was no uterine involvement [8].…”
Section: Discussionmentioning
confidence: 99%
“… 1 Other organ sites affected by ECD include the retroperitoneum, the cardiovascular and pulmonary systems, and the skin. 11 , 12 , 13 , 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…Perirenal soft tissue with a "hairy kidney" appearance can be commonly seen in cases of retroperitoneal involvement, often associated with perivascular infiltration of the abdominal aorta (65) (Fig 17). Renal and vascular structures are the most commonly affected abdominal organs, and perirenal infiltration is the most prevalent finding, noted in 67% of patients at CT and MRI (74). Recent studies have investigated the association between the imaging findings and the presence of BRAF V600E mutation.…”
Section: Cnsmentioning
confidence: 99%
“…Recent studies have investigated the association between the imaging findings and the presence of BRAF V600E mutation. In a prospective study of 61 patients with ECD who underwent CT or MRI for abdominal findings, there was a statistically significant association between BRAF V600E mutation and specific imaging findings, including perinephric infiltration (P = .003; OR, 7.27); renal sinus and pedicle involvement (P < .001; OR, 14.86); sheathing or stenosis of the prox-imal ureters (P < .001; OR, 8.84); hydronephrosis (P < .001; OR, 8.71); adrenal gland involvement (P < .001; OR, 8.56); periaortic infiltration (P = .03; OR, 3.96); sheathing or stenosis of the renal artery (P < .001; OR, 10.1); and sheathing of the celiac, superior mesenteric, or inferior mesenteric arteries (P = .04; OR, 4.40) (74).…”
Section: Cnsmentioning
confidence: 99%
See 1 more Smart Citation